2006
DOI: 10.4018/joeuc.2006070101
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Intention to Use Biometric Devices

Abstract: Protection of physical assets and digital information is of growing importance to society. As with any new technology, user acceptance of new software and hardware devices is often hard to gauge, and policies to introduce and ensure adequate and correct usage of such technologies are often lacking. Security technologies have widespread applicability to different organizational contexts that may present unusual and varied adoption considerations. This study adapts the technology acceptance model (TAM) and exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In the field of mobile payment, Shin (2010) suggested that convenience consists of easy handling, fast processing of payment transactions and easy learnability of the payment procedures. Several studies have demonstrated that convenience is a critical factor in determining the use of innovative technology and security systems (James et al. , 2006; Miltgen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of mobile payment, Shin (2010) suggested that convenience consists of easy handling, fast processing of payment transactions and easy learnability of the payment procedures. Several studies have demonstrated that convenience is a critical factor in determining the use of innovative technology and security systems (James et al. , 2006; Miltgen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the original TAM model has been criticized for its generalizability and failure to sufficiently predict in specific contexts and circumstances. That has provided an impetus for studies of BT to extend and adapt the model (Al-Harby, 2010; Alsamydai, 2014; Ami-Narh, Aziale, & Akanferi, 2014; Holden & Karsh 2010; James, Pirim, Boswell, Reithel, & Barkhi, 2006;Miltgen et al, 2013;Morosan, 2012b;Tassabehji & Kamala, 2009;Sumner, 2007). Adding additional factors or combining the model with other acceptance models can enhance the TAM specificity and explanatory utility (Szajna, 1996).…”
Section: The Technology Acceptance Modelmentioning
confidence: 99%
“…Accordingly, this paper emphasized the probable cause of success and failure factors that might influence passengers' repeat use intentions of biometric security, such as the perceived benefits, perceived risks, and initial use intention. Most previous studies on users' use intention of biometrics dealt with ease of use and usefulness [20,21], and other prior research approached the issue from the perspectives of innovation and security [22]. However, not many studies have attempted to analyze the problem from a diverse perspective, including the potential influence of perceived benefits, perceived risks, and initial use intention at the same time.…”
Section: Introductionmentioning
confidence: 99%